Answer:
i am in 7th grade
Step-by-step explanation:
The percent of decrease would be 60%
Step-by-step explanation:
well,
(y - 7)² = (y - 7)(y - 7)
remember how to multiply 2 expressions ?
you have to multiply every term of one expression with every term of the other expression and sum the results all up (incl. considering their individual signs, of course).
so, when we do the multiplication, we get
(y - 7)(y - 7) = y×y - 7×y - 7×y + (-7)×(-7) =
= y² - 14y + 49
and that is clearly different to y² - 49
FYI
y² - 49 is the result of
(y - 7)(y + 7)
because
y×y + 7×y - 7×y + (-7)(7) = y² - 49
Answer:
C. 189
Step-by-step explanation:
Each triangle is 27 which makes it 108, and 108+81=189
Answer:
Step-by-step explanation:
no